PERAN PENGASUHAN AYAH TERHADAP PERILAKU EMPATI ANAK USIA DINI: PERAN PENGASUHAN AYAH TERHADAP PERILAKU EMPATI ANAK USIA DINI - Mahkamah Brantasari (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
The involvement of the father in carrying out his role in good parenting will have a good influence on the social development of children, including a sense of empathy. Good parenting by fathers has an impact on cognitive, academic, psychological-emotional abilities and children's interactions in their social environment. Empathy itself is a feeling that a person has to share what others feel, understand the thoughts of others and want to help others who need it. This study uses a quantitative descriptive method, which takes a predetermined sample of 38 fathers who have children aged 4-6 years. This study uses several instruments in its measurement, namely: the role of fathers (X), Inventory of Father Involvement (IFI) and Empathy for early childhood (Y). In the ANOVA table there is an F count of 6.075 > from 0.05. In the normality test, it was found that the Asymp sign (2-tailed) stated that the standard residual of 0.102 in the test spread was normal. The calculation of the means table also shows that the behavior of empathy in early childhood has a linear calculation with the parenting role of the father. Until the correlation test also shows that there is a significant correlation, namely r = 0.019 > 0.05. From several data tests that have been carried out, all of them state that the parenting role of the father has an influence on the child's empathetic behavior.